'We all know why we're here': Learning as a community of practice on Access to HE courses. Issue 6 (1st November 2016) - James, Nalita; Busher, Hugh; Suttill, Beth
Abstract : This article examines the extent to which Access to Higher Education courses can be defined as communities of practice. Other studies have already revealed the importance of mutual engagement and supportive relationships between students and between students and tutors in facilitating learning. While previous studies carried out on Access to HE (AHE) courses in England and Wales have largely focused on single colleges, the study that this article draws on was carried out in three urban further education (FE) colleges using a linked case studies design and a social interactivist lens. It investigated mature students' perspectives of their changing learning identities through their developing relationships with their tutors and with each other during their AHE courses. Qualitative data was collected from five to six self-selecting AHE students in each college using focus group interviews and from their tutors using individual interviews. The findings suggest that the AHE students in this study generally participated and interacted in a supportive and collaborative way, guided by their tutors, and how and why they did this. This mutual engagement around particular core values helped to construct communities of practice, although some students remained peripheral participants. Within these communities were considerable inequalities of power, largely sustained by the institutional structures and professional discourses within which the AHE courses were located.